Factors Associated with Repeat Sexual Offending among U.S. Military Veterans Compared to Civilians. Issue 2 (3rd April 2022) - Brooks Holliday, Stephanie; Sreenivasan, Shoba; Elbogen, Eric; Thornton, David; McGuire, Jim
Abstract: Veterans have higher rates of incarceration for sexual offenses than non-veterans, but little is known about the factors associated with repeat sexual offending among veterans. This study used the Survey of Inmates in State and Federal Correctional Facilities to examine whether the factors associated with repeat sexual offending differ between veterans and non-veterans. In a multivariate logistic regression, there were significant interactions between veteran status and both age and race. Diagnosis of personality disorder and history of violation of conditional release were also associated with repeat offense status. Findings can help inform intervention and risk management with veterans.